2015
DOI: 10.3832/ifor1258-007
|View full text |Cite
|
Sign up to set email alerts
|

Soil chemical and physical status in semideciduous Atlantic Forest fragments affected by atmospheric deposition in central-eastern São Paulo State, Brazil

Abstract: © iForest -Biogeosciences and Forestry IntroductionThe Brazilian Atlantic biome is recognized as one of the hotspots for the conservation of biodiversity (Forzza et al. 2012), though it is severely affected by diverse human interferences, particularly in the State of São Paulo, southeastern Brazil (Domingos et al. 2003). The semideciduous Atlantic Forest is highly fragmented in central-eastern São Paulo because of the expansion of agriculture and urban and industrial growth (Nalon et al. 2008). Besides the red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 59 publications
2
6
0
1
Order By: Relevance
“…In agreement with many studies (e.g. Konen, Burras, & Sandor, 2003;Lopes et al, 2015;Telles et al, 2003), the negative correlation between SOC, STN and sand content was expected, because, generally, soils with a high content of sand are well aerated and tend to have low soil moisture content, which is due to a rapid decomposition and a low stabilization of the organic carbon (Baritz, Seufert, Montanarella, & Van Ranst, 2010;Telles et al, 2003). The significant and negative correlation between SOC and BD confirmed by many studies (e.g.…”
Section: Resultssupporting
confidence: 89%
“…In agreement with many studies (e.g. Konen, Burras, & Sandor, 2003;Lopes et al, 2015;Telles et al, 2003), the negative correlation between SOC, STN and sand content was expected, because, generally, soils with a high content of sand are well aerated and tend to have low soil moisture content, which is due to a rapid decomposition and a low stabilization of the organic carbon (Baritz, Seufert, Montanarella, & Van Ranst, 2010;Telles et al, 2003). The significant and negative correlation between SOC and BD confirmed by many studies (e.g.…”
Section: Resultssupporting
confidence: 89%
“…In turn, in the case of slopes under soil-protecting forests, significant positive correlation between SOCP and the content of potassium and magnesium were found. The negative correlation between soil organic carbon stocks and sand content is in agreement with many studies [53,54]. As indicated by Conforti et al [55], generally, soils with a high content of sand are well aerated and tend to have low soil moisture content, which is due to a rapid decomposition and a low stabilization of the organic carbon.…”
Section: Resultssupporting
confidence: 89%
“…1). One probable source of Fe to ryegrass in the MRC during the dry seasons was the resuspension of oxisol soils that are rich in such element according to Lopes et al (2015), due to the traffic in unpaved roads commonly observed in rural areas. Moreover, crop fertilization with compounds containing S, K and B in their composition and vinasse applications in sugarcane, with high K concentration (Christofoletti et al, 2013) generally occur at the end of the dry seasons, contributing to nutritional inputs and possibly imbalances to the bioaccumulator species and, by analogy, to the forest remnants that still exist in the study region.…”
Section: Spatial and Seasonal Nutritional Enrichments In The Study Rementioning
confidence: 99%